Investigating reading comprehension in English as additional language learners: children's processing of metaphors and internal inconsistencies when reading text - Hessel, A (2018)
English as an additional language (EAL) learners form a large group of students in UK schools and are known to differ from monolinguals, particularly in vocabulary and reading comprehension, but little is known about the way they process texts when reading. The three experiments presented in this thesis had three overarching objectives: first, to establish how children process different metaphors; second, to investigate how children monitor their comprehension; and third, to compare these reading processes between EAL learners and monolinguals. In Experiments 1 and 2, metaphor processing was compared across metaphor types (nominal and verbal) and between children with varying word knowledge. In Experiment 3, comprehension monitoring was associated with word knowledge and strategic awareness. Across all three experiments, language group differences were identified. Nominal metaphors were more challenging to understand for children than literal controls, a difficulty that stemmed from increased demands on post-lexical processing, as manifest in increased rereading. Children were able to monitor their comprehension on internal inconsistencies, which was demonstrated through selective rereading. Language group differences were evident relative to word knowledge. EAL learners were behind monolinguals in their metaphor processing relative to performance on standardised tests. Given sufficient word knowledge, EAL learners and monolinguals were, however, on a par in comprehension monitoring. For future research, the findings indicate that online tasks of reading processing hold valuable information about EAL learners’ reading comprehension. For teaching, results indicate the importance of supporting word knowledge to close language group differences and to support skilful reading processing.